Does traumatic occlusal forces lead to peri-implant bone loss? A systematic review - Martinna Mendonça BERTOLINI; Altair Antoninha DEL BEL CURY; Lucas PIZZOLOTO; Ivan Ronald Huanca ACAPA; Jamil Awad SHIBLI; Dimorvan BORDIN
Abstract Observational studies have indicated that crestal bone level changes at implants are typically associated with clinical signs of inflammation, but still mechanical overload has been described as possible factor leading to hard-tissue deficiencies at implant sites without mucosal inflammation. The aim of this paper was systematically review the literature regarding the possible effect of traumatic occlusal forces on the peri-implant bone levels. Literature search was conducted using PubMed, Scielo and Lilacs, including the following terms: oral OR dental AND implant$ AND (load OR overload OR excessive load OR force$ OR bruxism) AND (bone loss OR bone resorption OR implant failure$). Databases were searched for the past 10 years of publications, including: clinical human studies, either randomized or not, cohort studies, case control studies, case series and animal research. Exclusion criteria were review articles, guidelines and in vitro and in silico (finite element analysis) research, as well as retrospective studies. The PICO questions formulated was: "does traumatic occlusal forces lead to peri-implant bone loss?" The database searches as well as additional hand searching, resulted in 807 potentially relevant titles. After inclusion/exclusion criteria assessment 2 clinical and 4 animal studies were considered relevant to the topic. The included animal studies did not reveal an association between overload and peri-implant bone loss when lower overloads were applied, whereas in the presence of excessive overload it seemed to generate peri-implant bone loss, even in the absence of inflammation. The effect of traumatic occlusal forces in peri-implant bone loss is poorly reported and provides little evidence to support a cause-and-effect relationship in humans, considering the strength of a clinically relevant traumatic occlusal force.